The Effect of Additional Layers Parameters on the Modifided Bragg Waveguide Characteristics - Sashkova, Y. V.; Odarenko, E. N. (IEEE, 2017)
Bragg waveguide with additional layers between hollow core and periodic cladding is considered. On the base of dispersion equation solutions dispersion diagrams are obtained. The transversal spatial distributions of the electric field intensity are shown. The characteristics of Bragg waveguide respect to additional layer thickness and permittivity are considered. It is shown that increase of additional layers thickness results in increase of slow-waves number. Also field intensity decay in channel is reduced. Number of slow-waves increases respect to additional layers permittivity too. But distribution of the electric field intensity in the channel changes insignificantly. So one can tune additional layers parameters to get expected Bragg waveguide characteristics.
Keywords: Bragg waveguide; Additional layers; Dispersion equation; Mode field spatial distribution